Nintedanib exerts anti-pulmonary fibrosis activity via inhibiting TANK-binding kinase 1 (TBK1) phosphorylation. Issue 8 (4th January 2022) - Li, Manru; Zhou, Yu; Wang, Tiantian; Li, Menglin; Chen, Xiong; Zhang, Tiantai; Wang, Dongmei; Zhang, Jinlan
Abstract : We described a chemoproteomics approach to identify TBK1 as a key target of the multikinase inhibitor nintedanib in IPF. This insight may facilitate a better understanding of the functional mechanism of nintedanib for antifibrosis efficacy. Abstract : Since triple angiokinase inhibitor could not fully explain the anti-pulmonary fibrosis activity of nintedanib (NDNB), the chemoproteomic strategy was performed to identify TANK-binding kinase 1 (TBK1) as the key target of NDNB in human pulmonary fibroblasts (HPFs). Functionally, NDNB exerts anti-fibrosis activity through impairing the p-TBK1-mediated Yes-associated protein (YAP)/transcriptional cofactor with PDZ-binding motif (TAZ) nuclear translocation.